Synthesis and Characterization of Magnetic Fe3O4/Zeolite NaA Nanocomposite for the Adsorption Removal of Methylene Blue Potential in Wastewater Treatment - Ngoc Bich Thi Tran; Ngoc Bich Duong; Ngoc Long Le (Journal of Chemistry)
In this research, the magnetic Fe3O4/zeolite NaA nanocomposite (Fe3O4/ZA), Fe3O4 nanoparticles, and zeolite NaA have been synthesized by facile hydrothermal methods for adsorption removal of methylene blue from aqueous solution. The as-synthesized Fe3O4/ZA nanocomposite was characterized by X-ray diffraction (XRD), MicroRaman analysis, Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy, X-ray fluorescence (XRF), N2 adsorption isotherms (BET), and UV-VIS analysis. The results show that with a small weight loading of Fe3O4, the ∼3.3% Fe3O4/ZA sample exhibits a high adsorption capacity (∼40.36 mg·g−1) and removal efficiency (∼96.8%) compared to that of the zeolite NaA (∼32.99 mg·g−1 and 79.11%, respectively). Interestingly, the removal efficiency and the adsorption capacity increase rapidly with the increase of adsorption time (10–60 minutes) and Fe3O4 loading (∼3.3–9.3% wt.) in the Fe3O4/ZA composition. The adsorption mechanism of MB molecules of the Fe3O4/ZA can be addressed at the combination of the interaction between active sites on the surfaces and edges of the invert spinel ferrite Fe3O4 nanoparticles and zeolite NaA with MB molecules. Our approach provides a simple, efficient, and scalable synthesis process that render practical applications of the magnetic Fe3O4/ZA nanocomposite as a lower-cost adsorbent for wastewater treatment.